2022
DOI: 10.3389/fncel.2022.972144
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional abnormalities in induced pluripotent stem cell-derived oligodendrocytes of individuals with primary progressive multiple sclerosis

Abstract: Multiple sclerosis (MS) is the most common neurological disorder in young adults and is classically defined as a chronic inflammatory demyelinating disease of the central nervous system (CNS). Although MS affects millions of people worldwide, its underlying cause remains unknown making discovery of effective treatments challenging. Whether intrinsic or extrinsic factors contribute to MS initiation and progression is still unclear. This is especially true for primary progressive MS (PPMS), the rarest form of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…OLs are the myelinating cells of the CNS that are produced from OPCs and can proliferate and migrate to the lesion ( 36 ). Many studies have shown that OPCs and OLs can be normally produced from iPSCs of MS patients like healthy iPSCs ( 36 , 38 42 ). However, it is controversial whether there are differences in OPCs or OLs derived from iPSCs of healthy controls and MS patients.…”
Section: Msmentioning
confidence: 99%
See 2 more Smart Citations
“…OLs are the myelinating cells of the CNS that are produced from OPCs and can proliferate and migrate to the lesion ( 36 ). Many studies have shown that OPCs and OLs can be normally produced from iPSCs of MS patients like healthy iPSCs ( 36 , 38 42 ). However, it is controversial whether there are differences in OPCs or OLs derived from iPSCs of healthy controls and MS patients.…”
Section: Msmentioning
confidence: 99%
“…Exogenous addition of activators, such as laminin, bFGF, and down-regulated NG2/CSPG4, may reverse deficient migration of MS-iPSCs-derived OPCs, suggesting that early OPCs migration capacity may be a potential target for restoring remyelination and neurological function ( 36 ). Compared with controls, a transcriptome study showed that PPMS-OLs had several differentially expressed genes involved in cell adhesion, apoptosis, and inflammation ( 42 ). Notably, the inflammasome component Nlrp2 is highly up-regulated and may be a potential biomarker for disease phenotyping and progression in the cerebrospinal fluid ( 42 ).…”
Section: Msmentioning
confidence: 99%
See 1 more Smart Citation
“…Here we leveraged the unique opportunity iPSC technologies offer to address this issue by investigating human glial cells independent of the complex in vivo environment, which is chronically altered by inflammation and infiltration of peripheral immune cells. A handful of studies have investigated iPSC-derived neural progenitors and oligodendrocytes from people with MS; these studies used a limited number of lines (up to 3) and have produced conflicting reports on MS phenotypes in CNS cells [39][40][41][42][43] . Leveraging the NYSCF automated platform for iPSC derivation, we generated 22 lines including healthy controls, RRMS, SPMS and PPMS samples, differentiate them into glia-enriched cultures and performed single-cell transcriptome analysis.…”
Section: Ipsc-derived Ms Astrocytes Mirror Pathological Astrocytes In...mentioning
confidence: 99%
“…16.575826 doi: bioRxiv preprint oligodendrocytes, astrocytes, microglia, and endothelial cells) have been effectively used to model intrinsic cellular dysfunctions of MS. By studying these systems, abnormalities have been found in mitochondrial function, junction integrity, and the development of a (resting) inflammatory state. [16][17][18][19][20] Senescent features have been described in iPSC-NSCs derived from people with PMS by identifying a SASP that was found to inhibit oligodendrocyte progenitor cell differentiation into mature myelinating cells. 11 Cellular metabolism is a key component of senescence and disease-associated mechanisms.…”
Section: Introductionmentioning
confidence: 99%